A Fragment of Robert Burns: from his Letter to Robert Ainslie, 16 October 1788. Issue 2 (September 2021) - Grant, James
Abstract : This paper describes the background research on a fragment of a letter from Robert Burns to his great friend Robert Ainslie purchased at auction in Edinburgh in 2020. The author wished to determine the history of the fragment and whether it was possible to reunite the fragment with the rest of the letter. Though the details of the fragment's history over the last two hundred and forty years could not be fully determined the paper describes a fascinating story involving multiple auctions, a Victorian autograph album, one of Queen Victoria's ladies of the bedchamber and even, possibly, Sir Walter Scott. It establishes beyond reasonable doubt that this fragment is the signed end of another letter fragment to be found in the Edinburgh edition belonging to Robert Ainslie which is now in the G. Ross Roy Collection of Robert Burns in the University of South Carolina.